TINJAUAN YURIDIS ATAS AKTA PERJANJIAN KREDIT NOTARIS YANG WAKTU PENANDATANGANANNYA TIDAK DILAKUKAN SECARA BERSAMAAN OLEH PARA PENGHADAP - Dian Saputra (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACT In the implementation of the powers, duties and functions of the Notary, as the an authentic documents maker, trouble reading, and signing of deed by the parties have expressly provided for in Article 1 of Law Number. 2 of 2014 on amendments to the law No. 30 of 2004. But in practice, sometimes the signing of the Notary deed after reading is not always immediately signed by both parties, for reasons of time efficiency, the parties are running an emergency business, conduct meetings with shareholders for example. This was possible if the agreements have been executed by the parties and the Notary Public knows well with both the appear before. It needs to underline that signing the deed was done on the same date. Meanwhile, if carried out on different days, with minimized risk and legal consequences in the future should be given power of attorney specified in the deed or the deed attached to produce minutes, so the signing of the deed immediately after the reading of the deed. If not then the deed is made cannot be as valid evidence and irrevocable due to non-fulfilment of the terms subjective and objective of a treaty. For Notary as public official, he should consider tha provision of Article 16 of UUJN.Problems in the study include how the implementation of the provisions regarding the time of the deed signing by the penghadap [~ who appear before], witnesses and the Notary according to UUJN No. 2 of 2014 on amendments to the law No. 30 of 2004 in the practice and Notarial position upon deed is not done at the same time of its signing by the appear before.